2019
DOI: 10.3390/jcm8111841
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Liquid Biopsy Biomarkers from Aqueous Humor in Predicting Anti-VEGF Response in Diabetic Macular Edema: Results of a Pilot Study

Abstract: The objective was to investigate the usefulness of the “liquid biopsy” of aqueous humor (AH) to predict the clinical response after intravitreal injections (IVT) of anti-VEGF agents for treating diabetic macular edema (DME). For this purpose, AH samples obtained during the first anti-VEGF IVT from 31 type two diabetic patients were analyzed. Patients were classified into three groups according to their anti-VEGF response: rapid responders (n = 11), slow responders (n = 11), and non-responders (n = 9). In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 36 publications
(43 reference statements)
0
29
0
Order By: Relevance
“…This analysis is not without limitations. Although the Protocol T study was carried out with patients from the United States, the patient characteristics of anti-VEGF treated patients are very similar between Western countries, as shown in several published case series studies carried out in Europe and US [20][21][22][23][24][25][26]. A multicenter US study included patients treated with the 3 available anti-VEGF therapies with a mean age of 63.4 years and 80.8% with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis is not without limitations. Although the Protocol T study was carried out with patients from the United States, the patient characteristics of anti-VEGF treated patients are very similar between Western countries, as shown in several published case series studies carried out in Europe and US [20][21][22][23][24][25][26]. A multicenter US study included patients treated with the 3 available anti-VEGF therapies with a mean age of 63.4 years and 80.8% with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In another Spanish observational study that included patients treated with ranibizumab and aflibercept, the patients had a mean age of 69 years, 90% had type 2 diabetes, and they had a baseline visual acuity of 0.52 logMAR and a CST of 456 μm [ 25 ]. Additionally, a more recent study with anti-VEGF-treated type 2 diabetes patients showed similar baseline characteristics regardless of anti-VEGF responses with a mean age between 67.5 and 71 years, a mean BVCA of 62.5–67.2 letters and a mean CST from 443 to 542 μm [ 26 ]. All these patient characteristics could be considered similar.…”
Section: Discussionmentioning
confidence: 99%
“…Prognosis and response to treatment are two of the main points potentially addressed by the liquid biopsy approach. Recently, different studies have reported the response to DME treatment, by means of aqueous and vitreous samples [32,104,105,[111][112][113][114][115][116]. Sohn et al compared the AH concentration of VEGF and inflammatory molecules after the administration of triamcinolone and bevacizumab, showing that the first one was able to reduce several inflammatory molecules (IL-6, IP-10, MCP-1, PDGF-AA) and VEGF concentration, while bevacizumab just reduced VEGF concentration [32].…”
Section: Diabetic Macular Edema and Response To Treatmentmentioning
confidence: 99%
“…Combining PCR, GWC and Western blot technique increased the sensitivity by up to 97%[ 11 ] Increased levels of TGF beta- 2 in the AH could indicate an increased risk of secondary glaucoma in uveitis associated with juvenile idiopathic arthritis Levels of IL-10 (interleukin - 10) alone from an AH sample when more than 50 pg/ml can be can be a marker of intraocular lymphoma. [ 12 13 ] Cytokines, metalloproteinases and chemokines detected by ELISA in the AH are being studied for their diagnostic and prognostic significance as pro- or anti- inflammatory mediators in uveitis. [ 14 ] …”
Section: Anterior Chamber Paracentesismentioning
confidence: 99%
“…Levels of IL-10 (interleukin - 10) alone from an AH sample when more than 50 pg/ml can be can be a marker of intraocular lymphoma. [ 12 13 ] Cytokines, metalloproteinases and chemokines detected by ELISA in the AH are being studied for their diagnostic and prognostic significance as pro- or anti- inflammatory mediators in uveitis. [ 14 ]…”
Section: Anterior Chamber Paracentesismentioning
confidence: 99%